Shock hemorrhagic obstetric origin - Távara Orozco, Luis (2015)
We present an study of 49 cases on hemorrhage shock treated in Obstetrics and Gynocology Departament at Maria Auxiliadora Hospital Lima- Perú, from July 1. 1988 to December 31, 1989. In this period occurred 6,243 deliveries. The most frequent causes were ectopic pregnancy, abort and abruptio placentae. It is important also, then pregnancies were in first 12 weeks.  the management was: general measures and specific measures to treat the hemorrhage. There was I maternal death.